Does Covid-19 Degrade the Quality of Lecturing? A Research Evaluation on Multimedia Usage in Civil Engineering Lectures - Reni Karno Kinasih (Indonesian Journal Of Civil Engineering Education, 2022)
Due to Covid-19 lecturers must adopt an e-learning method, but some Civil Engineering subjects hypothesized can’t achieve outcome learning goals if delivered by e-learning method. This study is a contribution to mixed method research, integration of classroom action research method, evaluation questions, data analysis with statistical software and paradigm stances, and aims to explore the effectiveness of video usage in delivering courses. A questionnaire was distributed to 56 students, the data analyzed by Levene's Test and t-Test. The results obtained from Group 1 which received courses face-to-face had the quality of learning output with a standard deviation of -1,847 smaller than Group 2 which received courses through multimedia. The percentage of student approval as a respondent to the video is 95.5%.